Analysis of hourly global, direct and diffuse solar radiations attenuation as a function of optical air mass - Dal Pai, Alexandre; Escobedo, João Francisco [UNESP]; Martins, Dinival [UNESP]; Teramoto, Érico Tadao [UNESP] (Elsevier B.V., 2014)
The objective of this work is to verify the attenuation caused by atmospheric constituents through the relationship between global, direct and diffuse solar radiation with respect to optical air mass. The optical air mass change has spatial and temporal dependence and influences the radiation flux incident, causing changes in the average values. Global, diffuse and direct solar irradiances were provided by the Laboratory of Solar Radiometry of Botucatu-UNESP (latitude 22.9 degrees South, longitude 48.45 degrees West, altitude 745 m). The period assigned for the study comprised the years 2002 to 2006. The global solar radiation was measured by an Eppley PSP pyranometer. The direct solar radiation was measured by an Eppley Nip pyrheliometer attached to a ST-3 solar tracking system. The diffuse solar radiation was calculated by the difference between global and direct solar radiations. It was observed a decrease of solar radiation with the increase of optical air mass justified by the increase in probability of collision of solar rays with atmospheric constituents. For global solar radiation and optical air mass mo = 1, it was observed a minimum at 3.1 MJ/m(2) and a maximum of 4.1 MJ/m(2). For optical air mass mo=2, minimum at 1.5 MJ/m(2) and a maximum of 1.9 MJ/m(2). For direct solar radiation and optical air mass mo = 1, it was observed a minimum at 2 MJ/m(2) and a maximum of 3.8 MJ/m(2). For optical air mass mo=2, minimum at 1 MJ/m(2) and a maximum of 1.5 MJ/m(2). For diffuse solar radiation and optical air mass mo = 1, it was observed a minimum at 0.1 MJ/m(2) and a maximum of 1.5 MJ/m(2). For optical air mass mo=2, minimum at 0.1 MJ/m(2) and a maximum of 0.8 MJ/m(2). The joint analysis of data from direct and diffuse solar radiation allowed better understand of the attenuation process caused by the atmosphere, establishing qualitative relationships between absorption, scattering and reflection processes. (C) 2014 Published by Elsevier Ltd.
Keywords: Solar energy; Atmospheric attenuation; Scattering